1972
DOI: 10.1037/h0032163
|View full text |Cite
|
Sign up to set email alerts
|

Unsolved- and insoluble-problem behavior.

Abstract: One of the features of hypothesis-testing theories has been the concept of sampling from a finite set of hypotheses (Hs). This has led to interest in two related questions: (a) Why do 5s fail to solve a problem ? Previous data have suggested that 5s fail to solve because the solution H is not in their subset (the missing H assumption), (b) What happens when all the Hs S is testing are disconfirmed (i.e., when the subset goes to zero) ? One possibility is that 5s will resample the subset again (the recycling as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A variety of studies verified this , assumption Erickson & Zajkowski, 1967;Erickson, Zajkowski, & Ehmann, 1966;Guy, Van Fleet, & Bourne, 1966;Holstein & Premack, 196S;Trabasso & Bower, 1966). The second component of this statementthat a correct response should be at chance level-is challenged by the findings of Levine and his associates (Classman & Levine, 1972;Levine, 1971;Levine, Miller, & Steinmeyer, 1967;Levine et al, 1968). They have consistently found that the probability of a correct response, prior to solution, is between .3 and .4, when chance is .5.…”
Section: All-or-nonementioning
confidence: 98%
See 3 more Smart Citations
“…A variety of studies verified this , assumption Erickson & Zajkowski, 1967;Erickson, Zajkowski, & Ehmann, 1966;Guy, Van Fleet, & Bourne, 1966;Holstein & Premack, 196S;Trabasso & Bower, 1966). The second component of this statementthat a correct response should be at chance level-is challenged by the findings of Levine and his associates (Classman & Levine, 1972;Levine, 1971;Levine, Miller, & Steinmeyer, 1967;Levine et al, 1968). They have consistently found that the probability of a correct response, prior to solution, is between .3 and .4, when chance is .5.…”
Section: All-or-nonementioning
confidence: 98%
“…There is actually some evidence suggesting that subjects are not aware of all the potential hypotheses either at the beginning, or during the course, of the experiment. Levine discovered that some subjects actually omit an entire dimension from consideration and that this creates a functionally unsolvable problem for them (Glassman & Levine, 1972;Levine, 1971;Levine, Yoder, Kleinberg, & Rosenberg, 1968). This phenomenon is covered more thoroughly later under a discussion of dimensional sampling.…”
Section: Basic Assumptions Prior Knowledge Of Hypothesis Poolmentioning
confidence: 99%
See 2 more Smart Citations